واقع الاستثمار في الطاقات المتجددة في الجزائر -مع الأخذ بالتجربة الألمانية- - أوبختي, نصيرة; بوجنان, التوفيق (جامعة الوادي University of Eloued, 2019)
يتزايد الاهتمام بدراسة موضوع الطاقات المتجددة كونها تمثل إحدى أهم المصادر الرئيسية للطاقة العالمية خارج الطاقة التقليدية فضلا عن كونها طاقة نظيفة و غير ملوثة للبيئة مما يكسبها أهمية بالغة نحو تحقيق التنمية المستدامة، و هو ما نحاول إبرازه من خلال هذه الدراسة و ذلك بتسليط الضوء على أهم المشاريع الهامة في المجال.علاوة على رصد التجربة الألمانية و محاولة الاستفادة منها كما تشير التوقعات إلى أن هذه الطاقة الخضراء ستلعب دورا هاما في المستقبل، الأمر الذي لا شك فيه أنها ستلعب دورا رياديا في تحقيق التنمية المستدامة في الجزائر بصفة خاصة. The interest in subject of renewable energy is increasing day after day because it represent one of the most important sources of global energy out the classical energy preferred about as a clean energy and not pollutant for environment, on which it gains a profound importance through achieving the sustainable development, that what we would like to show it through this study, in addition to envision the experience of Germany in the field and trying to learn from it, then mastery the light on the most efficient project in that domain. All the expectations indicate that renewable energy will play an increasing role in future. Therefore it will play a leading role in achieving the sustainable energy especially in Algeria.
The reality of investment in renewable energies in Algeria With the German experience
مقال
Keywords: طاقة – طاقة متجددة – مشروع ديزرتك-تجربة ألمانيا.